Sikh diasporic negotiations: Indian and Canadian history in Can You Hear the Nightbird Call?. (2nd January 2018) - Bhat, Shilpa D.
ABSTRACT: The perceived interconnection of Sikh religion and extremism, and the mistaken association of Sikhism with Islam impacted Sikh consciousness and historically, these have presented challenges to Sikh identity, representation, and intercultural negotiations in Canada. With reference to Anita Rau Badami's Can You Hear the Nightbird Call? (2010), this article investigates Canadian Sikh diaspora's collective memories, specifically: (i) the return of the Komagata Maru ship from Vancouver (1914) (ii) partition of India (iii) the death of passengers in Air India 182 (23 June 1985) from Toronto to India; (iv) Operation Blue Star (1984) and (v) the 1984 Sikh carnage.